A female patient with a history of uterine surgery exhibiting a large uterine diverticulum complicated by abnormal uterine bleeding: a case report - Jiao, Haining; Zhu, Lan; Shen, Yuhong (Journal of the Pakistan Medical Association, 2025)
The main symptoms of a previous caesarean uterine scar diverticulum include abnormal uterine bleeding, chronic pelvic pain, and caesarean scar pregnancy. At present, laparoscopy combined with hysteroscopy has a clear surgical field, which allows accurate access to the uterine incision site under direct vision, thus effectively reducing bladder damage and repairing myometrial tissue. A 37-year-old woman who had undergone a caesarean section 7 years prior reported vaginal bleeding for more than 1 year. The diagnosis of a large uterine diverticulum was confirmed by magnetic resonance imaging and ultrasound. Laparoscopy combined with hysteroscopy was performed to repair the uterine scar diverticulum defect and recover the anatomy of the uterine isthmus. The surgery was successful, and the patient recovered well. There was no interphase bleeding at the 3-month follow-up. Laparoscopic folding and docking sutures combined with hysteroscopy are appropriate treatment options. Keywords: Caesarean section, Uterine diverticulum, Abnormal uterine bleeding, Laparoscopy, Hysteroscopy.